ADDITION OF THIAMIN AND LEAF FOLIAR IN ABACA BANANA (Musa textillis Nee.) ACCLIMATIZATION - Rina Srilestari; Suwardi Suwardi (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
The economic value of the Abaca banana is on the trunk which contains fiber for valuable textile and paper industry raw materials. The multipurpose fiber and its prospects are quite good, so the abaca plant gets a lot of attention from various community groups both private, state-owned, cooperative and farmers. Propagation through multiplication humps is very low, planting material is easily damaged in transportation, is not durable and requires large space so that transportation costs are high. One alternative to overcome the provision of healthy, large and fast seedlings is to use seedlings from tissue culture. The aim of the study is to get the right thiamin and leaf fertilizer concentrations at the acclimatization stage. The experimental design used was a 2-factor Complete Randomized Design, Thiamin concentration (1 ml / l, 2 ml / l, 3 ml / l) and leaf fertilizer (0.5 ml / l, 1 ml / l, 1.5 ml / l). The data obtained were analyzed for diversity at 5% level and further tests using Duncan Multiple Range Test (DMRT) level of 5%. The results showed no interaction between thiamin and leaf fertilizer, Thiamin 2 ml / l gave the best results on all parameters and 1.5 ml / l leaf fertilizer could increase plant height and the number of leaves of abaca banana plants.Keywords: Thiamin, leaf fertilizer, abaca banana, acclimatization